1959
DOI: 10.1002/j.1537-2197.1959.tb07003.x
|View full text |Cite
|
Sign up to set email alerts
|

Indole Acetic Acid Oxidase and Peroxidase Activities in Normal and Crown Gall Tissue Cultures of Parthenocissus Tricuspidata

Abstract: Lipetz, Jacques, and Arthur W. Galston. (Yale U., New Haven.) Indole acetic acid oxidase and peroxidase activities in normal and crown gall tissue cultures of Parthenocissus tricuspidata. Amer. Jour. Bot. 46(3) : 193‐196. Illus. 1959.—Normal and crown gall cells of P. tricuspidata grown in pure culture were examined for IAA oxidase and peroxidase activities. No IAA oxidase activity could be demonstrated in dialyzed or undialyzed homogenates of either tissue; however, crown gall tissue, but not normal tissue, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1961
1961
1981
1981

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…As the tissues were routinely grown on a medium lacking exogenous IAA, it was possible that the enzyme was not induced. Therefore, sam- Lipetz and Galston (8) suggested that 1 of 2 or more components of the IAA oxidase system of Parthenocissus crown-gall tissue cultures is destroyed or inactivated when the tissue is homogenized. This observation is based upon the destruction of IAA by intact tissue in a reaction mixture containing Mn+ + and DCP, but lack of destruction by homogenates of the same tissue.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the tissues were routinely grown on a medium lacking exogenous IAA, it was possible that the enzyme was not induced. Therefore, sam- Lipetz and Galston (8) suggested that 1 of 2 or more components of the IAA oxidase system of Parthenocissus crown-gall tissue cultures is destroyed or inactivated when the tissue is homogenized. This observation is based upon the destruction of IAA by intact tissue in a reaction mixture containing Mn+ + and DCP, but lack of destruction by homogenates of the same tissue.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the paucity of references attesting to the demonstration of IAA oxidase in plant tissue cultures (see, however, refs. 8,11,12,17), the simplest assumption to explain the behavior of the Ephedra tissue is that the tissue produces an IAA oxidase which destroys the IAA, but not the 2,4-D or NAA.…”
mentioning
confidence: 99%
“…DISCUSSION ENZYME LOSS FROM TISSUES: The release of enzymes and other substances from plant tissue cultures has been extensively documented. Among the enzymes released from these tissues are amylase (22), acid phosphatase (23), indole acetic acid oxidase (24) and peroxidase (25). Although variations in the magnitude of such losses exist, it is fairly well agreed that tissue cultures derived from plants or animals are "leaky.…”
Section: Localization Of Peroxidasementioning
confidence: 99%
“…This difference in the two types of tissue has been the object of investigation for the last 10 years, and the possibilities for speculation have been narrowed. Several investigators have ruled out the possibility that the crown gall grows without auxin altogether (3,4). Therefore, the only remaining possibilities are that the auxin is produced more rapidly in the crown gall, that it is destroyed less rapidly, or that the tumor has a much lower auxin requirement.…”
mentioning
confidence: 99%